1999
DOI: 10.1046/j.1365-2141.1999.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

P53 deletion is not a frequent event in multiple myeloma

Abstract: Summary. Recently a high incidence of interstitial deletion of the P53 locus has been reported in multiple myeloma (MM) patients. Considering the importance of such an event, we analysed 79 patients with advanced-stage disease usinḡ uorescence in situ hybridization (FISH). Strikingly, we found only 7/79 patients with a P53 deletion. In order to rule out any differences in probe selection, we reanalysed all the patients with the same probe as that used in a previous study, and con®rmed the low incidence of P53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 11 publications
7
43
0
3
Order By: Relevance
“…These analyses are in good agreement with genetic and cytogenetic studies, that generally imply p53 defects in about 10% of medullary myeloma cases, but report higher incidences for patients with plasma cell leukemia. [17][18][19][20] Our observations confirm the target specificity of nutlin-3a and clearly demonstrate the p53 dependence of the observed biological effects. These experiments suggest that the downstream components of the p53 pathway appear to be at least partially intact in more than 90% of primary medullary MM cases.…”
Section: Nutlin-mediated P53 Induction In Multiple Myelomasupporting
confidence: 80%
“…These analyses are in good agreement with genetic and cytogenetic studies, that generally imply p53 defects in about 10% of medullary myeloma cases, but report higher incidences for patients with plasma cell leukemia. [17][18][19][20] Our observations confirm the target specificity of nutlin-3a and clearly demonstrate the p53 dependence of the observed biological effects. These experiments suggest that the downstream components of the p53 pathway appear to be at least partially intact in more than 90% of primary medullary MM cases.…”
Section: Nutlin-mediated P53 Induction In Multiple Myelomasupporting
confidence: 80%
“…The karyotypic abnormalities often, but not always, juxtapose c-myc and an Ig enhancer, with 9/25 (36%) of MM cell lines and 8/17 (47%) of primary tumors having a karyotypic abnormality of c-myc that does not involve an apparent association with an Ig enhancer. By interphase FISH analyses, it is reported that c-myc is associated with the IgH locus in 3/140 MM tumors representing all stages, and in none of 79 MGUS tumors (Avet-Loiseau et al, 1999b). Cloned t(8;14) translocation/insertion breakpoints often do not occur at the IgH sites targeted by the three B cell speci®c DNA modi®cations.…”
Section: Dysregulation Of C-myc As a Paradigm For Secondary Translocamentioning
confidence: 99%
“…Interphase FISH analyses using probes that¯ank an Ig locus to detect split signals or a probe from one end of an Ig locus together with a probe from a speci®c chromosomal region to detect fusion signals permit a comprehensive assessment of Ig translocations in all tumor cells, including MGUS. To minimize the signi®cant background problems with interphase FISH assays, tumor cells have been enriched by pre-selection (e.g., CD-138 magnetic bead selection), or by restricting analysis to cells that express cytoplasmic kappa or lambda IgL (Ahmann et al, 1998;Avet-Loiseau et al, 1999b).…”
Section: Identi®cation Of Ig Translocations In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…p53 is inactivated in 10-12% of MM cases (Avet-Loiseau et al, 1999;Chng et al, 2007) resulting from either p53-DNA binding domain mutations or overexpression of murine double minute 2 gene (MDM2) (Farnebo et al, 2010). MDM2, an E3-ubiquitin ligase, binds p53 to ubiquitinate and targets it for degradation through ubiquitin/proteasome pathway (Piette et al, 1997).…”
Section: Deregulation Of Cell Cycle and Apoptosis Mechanismsmentioning
confidence: 99%